MIMESIS PADA GAMELAN WANDA ANYAR - Sopian Triana (LP2M ISBI Bandung, 2018)
Koko Koswara (Mang Koko) which is a reformer figure in Sundanese music (karawitan) able to create a new genre art that remains oriented to the aesthetics of Sundanese gamelan. The genre is called Gamelan Wanda Anyar created around the 70s. The authors are interested to study the instrument / gending of this art which has a dynamic musical form structure. The phenomenon of sound that occurs in Gamelan Wanda Anyar dish stimulates the writer to trace it further in both textual and contextual. In dissecting this case the author uses the aesthetic theory that Aristotle devised about mimesis (imitation). The purpose of this paper is to provide cm overview of the work of Mang Koko mean poured in the Gamelan Wanda Anyar which until now is still a benchmark of the artists in developing Sundanese music(karawitan)